2010
DOI: 10.1111/j.1745-4530.2008.00327.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluidized Bed Drying of Corn, Bean and Chickpea

Abstract: In the agricultural industry, drying is a very important process to preserve food products. Also, fluidized bed drying is the most common preferred process due to its advantages. In this paper, the effects of the fluidizing air temperature and velocity on the drying performance of corn, beans and chickpeas were investigated by carrying out a series of tests. Laboratory‐scaled fluidized bed drying apparatus was used. Batch drying experiments were conducted by applying three different air temperature and two dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…Many authors [3,4,5,6,7,8,9,10,11,12] have observed in agricultural products the absence of constant drying rate stage as well as a decrease on this rate value starting from the initial drying process. These results indicate that the material surface is not initially saturated with water, and the rate of internal moisture movement controls the drying rate during most of the process [13] .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Many authors [3,4,5,6,7,8,9,10,11,12] have observed in agricultural products the absence of constant drying rate stage as well as a decrease on this rate value starting from the initial drying process. These results indicate that the material surface is not initially saturated with water, and the rate of internal moisture movement controls the drying rate during most of the process [13] .…”
Section: Introductionmentioning
confidence: 97%
“…Several studies have also revealed that air temperature has strong influence on drying rates enhancing their values [3,4,5,6,7,8,9,10,11,12,15,16,17,18] . However, drying processes at high temperatures can deteriorate the product quality by increasing temperature and moisture gradient leading to internal tensions, cracks, breakages, and fractures in the grain [16] .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Fluidized bed granulation is often a method of choice for drying heat-sensitive compounds, including microbial cultures. Advantages, such as good temperature control, equal temperature distribution, high drying capacity, short drying time, low maintenance costs, and large-scale production, are noticeable [15][16][17][18]. To minimize the damage caused by drying and to achieve increased bacterial viability in storage time, fluidized bed immobilization of LAB is mainly performed in the presence of protective carbohydrates [15].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the sample that was not treated contained 2–8 times the FFA content of the treated sample, depending on the heating temperature and period. Drying black glutinous rice by the high temperature fluidization technique efficiently reduced the moisture of the paddy after harvest and could likely be applied to inactivate the lipase enzyme before storage because of the high temperature (Chandrasekhar and Chattopadhyay ; Soponronnarit and Prachayawarakorn ; Cil and Topuz ). Up until the present, data on the change in the FFA content during storage of black glutinous rice dried by the fluidization technique had not been reported.…”
Section: Introductionmentioning
confidence: 99%